LINC00518 Interference Inhibits Non–Small Cell Lung Cancer by Upregulating miR216b-5p Expression - Ren Y; Zhu H; Han S (Cancer Management and Research, 2020)
Yuanyuan Ren,1,2,* Huadong Zhu,3,* Song Han4 1Department of Oncology, People’s Hospital of Taizhou, Taizhou, Jiangsu Province 225300, China; 2Department of Oncology, Hospital 5, affiliated with Nantong University, Taizhou 225300, China; 3School of Life Science, Nanchang University, Nanchang, Jiangxi, 330031, China; 4Department of Cardiothoracic Surgery, Affiliated Suzhou Science and Technology Town Hospital of Nanjing Medical University, Suzhou, Jiangsu 215153, China*These authors contributed equally to this workCorrespondence: Song HanDepartment of Cardiothoracic Surgery, Affiliated Suzhou Science and Technology Town Hospital of Nanjing Medical University, Suzhou, Jiangsu 215153, ChinaTel +86 512-6958-8712Email hansong256@163.comIntroduction: Non–small cell lung cancer (NSCLC) accounts for the majority of lung cancer cases, and effective treatment for this disease is still lacking. This study aimed to explore the potential role of LINC00518 and miR216b-5p on cell proliferation and tumor growth in NSCLC.Methods: The expression of LINC00518, miR216b-5p, MMP7, and MMP9 in NSCLC cell lines was determined by RT-qPCR analysis, which was also used to confirm the transfection effects. After transfection, proliferation, clone-formation ability, migration, and invasion of NSCLC cells were detected by CCK8, clone-formation, wound-healing, and transwell assays, respectively. Western blot analysis was used to detect the expression of MMP7, MMP9, Ki67, and PCNA. A xenograft model was constructed by subcutaneous injection of transfected NSCLC cells into nude mice.Results: The results indicated that LINC00518 expression was increased and miR216b-5p expression decreased in NSCLC cell lines, and A549 cells were chosen for the next experiments. LINC00518 interference inhibited proliferation, invasion, and migration of A549 cells, together with the progression of NSCLC in vivo. In addition, LINC00518 directly targeted miR216b-5p. Downregulation of miR216b-5p weakened the inhibitory effect of LINC00518 interference on proliferation, invasion, and migration of A549 cells, as well as progression of NSCLC in vivo.Discussion: In conclusion, LINC00518 interference inhibits NSCLC, which is partially reversed by downregulation of miR216b-5p expression.Keywords: LINC00518, non–small cell lung cancer, miR216b-5p, proliferation, invasion and migration